TINGKAT KEPUASAN KONSUMEN TERHADAP KUALITAS PRODUK WARUNG BAKMI LETHEK SUMARAH BANTUL YOGYAKARTA DI TENGAH PANDEMI COVID-19 - Dwi Yoso Nugroho; Joko Triyono (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2021)
The Covid-19 pandemic requires all industries to be more creative and think hard in generating businesses that have been disrupted by this disaster. One of them is the tourism industry in which there is a food and beverage business that must pay more attention to the quality of its products. Because the quality of the product is needed by consumers, especially in these conditions. So to know the level of customer satisfaction to the quality of lethek noodle products sold in Warung Bakmi Lethek Sumarah Bantul Yogyakarta and analyze the attributes that are considered important needed improvement to improve customer satisfaction and even support the progress of culinary tourism in the local area. So the author examined with gap alisis method and IPA method. Informants in this study are consumers of Warung Bakmi Lekthek Sumarah taken with incidental sampling techniques with a total of 100 people. From this study produced an average value of Important Perfomance at 96.27%, where the figure in the category is not satisfactory . For gap analysis results, negative numbers (-) are obtained for menu variation variables, dish portions, food servings, and price variables. A negative sign means that the reality score received by the consumer is below the expected score. From the results of the analysis above, it is expected that the owner and manager of Warung Bakmi Lethek Sumarah pay more attention to the variables above.Keywords: Consumer Satisfaction Level, Product Quality and Covid-19 Pandemic